SOCIALLY RESPONSIBLE CITY PLANNING: A NEW STRATEGY FOR INCREASED SAFETY? - Stankevice, Inga (European Scientific Journal, ESJ, 2014)
A city is a complex dynamic system that includes economic, social, cultural, environmental, political, engineering, etc. aspects. The ideas of new urbanism and smart growth have emphasized urban spatial structure as an important player in social interactions. Hence, it is not accidental that new trends of research focus on one of the most important prerequisites of high quality of life – our safety. Therefore, a truly smart city, beyond other elements, includes a socially-oriented spatial structure, i.e. socially-responsible city plan. The research on the topic has proliferated in a limited number of countries. Thus, the paper contributes to the recognition of the potential of urban spatial structure in inhibiting crime. For this purpose, an empirically-based case study of Kaunas city located in Lithuania is presented and discussed.